Examining the Reciprocity in Dyadic Teacher-Child Relationships: One-With-Many Multilevel Design - Gregoriadis, Athanasios; Vatou, Anastasia; Tsigilis, Nikolaos; Grammatikopoulos, Vasilis (Frontiers in Education, 2022)
Recent literature has shown the reciprocal influences of teacher-student relationships for both teachers and students in primary school. When it comes to early childhood education, very few studies have examined the level and the nature of agreement between teachers’ and students’ perceptions for their dyadic relationships. Using the one-with-many model (OWM), a dyadic analysis approach, the present study aims to examine the degree of agreement between teachers’ and students’ perceptions about their dyadic relations. The Student-Teacher Relationship Scale (STRS) and the Child Appraisal of the Relationship with the Teacher Scale (CARTS) are used to assess the quality of teacher–student dyadic relationships from teachers’ and students’ perceptions, respectively. The dyadic sample (N = 1345 teacher-student dyads) is recruited from 168 preschool classrooms in Greece. Results of the OWM analysis showed that that teachers and students evaluated their dyadic relationship quality in a different way and there is no reciprocity in their views. Implications of the study’s results are also discussed.